UNDERSTANDING AND CLASSIFICATION OF SELF-DEFENSE CONDITIONS FOR THE FULFILLMENT OF CONTRACTUAL OBLIGATIONS - Mkrtchyan, Anna (State and Law, 2023)
The revelation of the interconnectedness, similarities between self-defenseand contract obligations institutes aimed to develop the practical application of these institutions in private law. The article reflects the de facto actions taken during the right of self-defense and the legal aspect of unilateral refusal of contractual arrangements. Non-jurisdiction methods of protection of rights as well as protection of contractual legal relationship have been discussed. We propose to enshrine the definition of the right to self-defense in the provisions of the general part of the civil legislation. In all other cases, to define applicable methods for each institution of private law.